2020
DOI: 10.3233/thc-209050
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measures of postural tremor at the upper limb joints in patients with essential tremor

Abstract: BACKGROUND: It is important to quantitatively assess tremor for accurate diagnosis and evaluation of the response to interventions in patients with essential tremor (ET). OBJECTIVE: The purpose of this study was to investigate the relationship between quantitative measures of postural tremor and clinical rating scale in patients with ET. METHODS: 18 ET patients performed a postural tremor task that required them to hold their arms outstretched parallel to the floor while wearing a gyro sensor based measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…Additionally, Heldman et al found a correlation of -0.78 between RMS angular velocity values and the modified bradykinesia rating scale[101] and Salarian et al found good correlation between RMS angular velocity values and the UPDRS bradykinesia subscore, as well as good correlation between RMS angular velocity of the roll axis and the tremor subscore of the UPDRS[52]. In patients with tremor, spearman correlation between RMS angular velocity and tremor severity scores ranged from 0.19 (finger-tonose) to 0.73 (keeping arms extended in front of the body) for Lopez-Bianco et al[108] and between 0.41 and 0.70 for Kwon et al[110], whereas Heo et al found lower RMS angular velocity values after electrical stimulation[105].Seventeen studies reported mean acceleration as a feature, but only two PD studies and one ataxia study discussed its sensitivity. Romano et al found lower mean acceleration for PD patients in comparison with the control group, while Zwartjes et al did not find significant differences between ON and OFF stimulation states of deep brain stimulation[57,90].…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Additionally, Heldman et al found a correlation of -0.78 between RMS angular velocity values and the modified bradykinesia rating scale[101] and Salarian et al found good correlation between RMS angular velocity values and the UPDRS bradykinesia subscore, as well as good correlation between RMS angular velocity of the roll axis and the tremor subscore of the UPDRS[52]. In patients with tremor, spearman correlation between RMS angular velocity and tremor severity scores ranged from 0.19 (finger-tonose) to 0.73 (keeping arms extended in front of the body) for Lopez-Bianco et al[108] and between 0.41 and 0.70 for Kwon et al[110], whereas Heo et al found lower RMS angular velocity values after electrical stimulation[105].Seventeen studies reported mean acceleration as a feature, but only two PD studies and one ataxia study discussed its sensitivity. Romano et al found lower mean acceleration for PD patients in comparison with the control group, while Zwartjes et al did not find significant differences between ON and OFF stimulation states of deep brain stimulation[57,90].…”
mentioning
confidence: 90%
“…Twelve studies included patients with essential tremor [102][103][104][105][106][107][108][109][110][111][112][113] and 11 included adults post-stroke [15,28,[114][115][116][117][118][119][120][121][122], whereas six included adults with MS [123][124][125][126][127][128]. One study included adults with HD and eight studies included children or adults with ataxia [29,[129][130][131][132][133][134][135][136].…”
Section: General Informationmentioning
confidence: 99%
See 3 more Smart Citations